Diets in eastern Gangetic Plains of South Asia: Brief assessment of sources and a comparison with the EAT-Lancet recommendations - Choudhary, Vishruta; Kishore, Avinash (International Food Policy Research Institute, 2019)
Food is as much an environmental issue as it is a health issue. What we eat and how we produce it has a tremendous impact on both human and planetary health. Most Global Burden of Disease risk factors are linked to diet (Figure 1) (Afshin et.al. 2019). At the same time food production, processing and trade also affect multiple environmental variables like freshwater resources, soil quality, forest cover, biodiversity, coastal eutrophication, and climate change. Our existing food system is unhealthy not only for humans but also for the environment. This is the point of departure for the EAT-Lancet Commission.